PERANAN LEMBAGA PEMASYARAKATAN DALAM MEMBINA DAN MENANGGULANGI NARAPIDANA RESIDIVIS DI WILAYAH HUKUM KOTA DUMAI - Eko Saputra; Erdianto '; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Penitentiary not only as a place to simply convict people, but also as a place to build also to educate the convicted people, so that later after they finish the criminal have the ability to adjust to life outside the penitentiary as a good citizen and obedient To the applicable law. However, in reality today, the coaching is not optimal and will make a seed of deeds that can be repeatedly done so that they will return to the coaching for a second time. In the case of placement and guidance, it should be necessary for perpetrators who perpetrate a recurrent crime (recidivist) should be differentiated from placement and guidance with prisoners who first enter into a penitentiary. It aims to prevent the inmates from having a first-time incident to commit another crime after being released, but unfortunately this has not yet been done.The purpose of this thesis writing, namely: first, assess the role of correctional institutions in fostering and tackling inmates residivis in Dumai City Legal Territory. Secondly, to know the constraints of correctional institutions in fostering and overcoming prisoners of residivis in the Dumai City Legal Territory. This type of research is a sociological or empirical legal research, ie research obtained directly from the community or primary data research.From the results of research problems there are two main things that can be concluded. First, prisons in fostering and tackling prisoners of recidivists perform two ways, the first coaching from within the wall and the second coaching from outside the wall. Second, constraints of correctional institutions in conducting coaching are, lack of awareness and discipline of the inmates themselves, as well as lack of discipline and assertiveness of officers in the process of coaching. Suggestion writer, first, pay more attention to coaching process and guidance which done in prison. Secondly, it further enhances the sense of discipline of prisoners in the process of guidance and counseling, and improve the quality of work and discipline prison officers in the process of coaching.Keywords: Penitentiary - Fostering - Residivist Prisoners